Critical Analysis of Station Area Development on PRASA owned land: The case of the Northern Corridor Railway Line Cape Town - Jonathan, Lesley-Anne Maria (Department of Construction Economics and Management, 2023)
The presence of well-located vacant land parcels within a city plays a contributing factor towards undermining the urban form and purpose of a well-run city. Property developers who seek out land for development in South Africa are limited to options of well-located small vacant land parcels or land parcels with existing developments that do not quite meet the demands within the property market. The presence of vacant rail station land parcels within South African cities provide an opportunity for improved urban form through the development of these prime locations. In the past the Passenger Rail Agency of South AFRICA (PRASA) have undergone the development of a restricted number of these land parcels, however given the total number of stations in South Africa the number of developed station area land parcels has been limited. The Northern Corridor railway line in Cape Town includes twenty-six rail stations, twenty of which are owned by PRASA, and the other six are owned by Transnet. The twenty PRASA owned rail stations include a total of 72 hectares of vacant station land parcels along the line with only two stations, with a total of 16 hectares between them, having seen progress towards development to date. This research has identified a gap in South African academic research that critically analysis the lack of development at vacant station land parcels in South Africa, and thus focus' in on the Northern Corridor as a case study, with particular attention on PRASA owned land parcels. This research seeks to answer the question of, why have real estate developments not been enabled and located at stations along the Northern Corridor railway line in Cape Town? Which is done through a literature review that unpacks theory on property development processes, Transit Oriented Development (TOD) and the Transport land use feedback cycles. Furthermore, the paper has made use of international precedent studies and empirical research to inform the research, and seeks to critically analysis legislative and policy pieces that govern and influence how station area land parcels are developed and managed in South Africa, and Cape Town in particular. These reviews provided valuable input into the design of the semi-structured interview questionnaires that were used as the basis of my research interviews. Through the completion of twelve semi structured interviews the primary data had been collected for this research, which informed the findings chapter for this paper and predominantly was used to provide direct insights to answering the research question put forward in this paper. Using these insights, proposals are made that PRASA together with the City of Cape Town and the Western Cape Provincial Government could apply towards improving the development of station area land parcels along the Northern Corridor.